Characteristics of behavioural regulation in children with autism spectrum disorder during performing memory and recognition tasks - Maksimova, Mariia; Hura, Andrii (Psychosomatic Medicine and General Practice, 2026)
Relevance. Autism spectrum disorder is one of the most widely discussed neurodevelopmental disorders, most commonly diagnosed in childhood. People with this disorder fall into the category of those with special educational needs. Under the law, this category requires additional support in the organisation of the learning process. Ukraine is making rapid progress in the development of inclusive education and creating safe learning environments. Effective organisation of this process requires an understanding of the nature of the deficit, particularly in terms of cognitive functioning. Research into the characteristics of activity regulation in this context may be useful for adapting educational programmes and increasing the effectiveness of learning for children with autism spectrum disorder. Objective. To investigate the impact of behavioural strategies on task performance in children with autism spectrum disorder. Methods. The study involved 50 children aged 5–6 years attending pre-school educational institutions. Of these, 25 had a confirmed diagnosis of autism spectrum disorder and 25 were neurotypical children. The main tool was the ‘Memorisation and recognition of two groups of three real images’ technique, designed for children aged 5–8 years, taken from the ‘Album for Neuropsychological and Pathopsychological Research of Children and Adults’. Mathematical and statistical methods were used to analyse the results. Results. Statistical analyses revealed a positive correlation between voluntary regulation strategies and performance levels during task execution, particularly under repeated cognitive load. Conclusions. The study found that children with autism spectrum disorder demonstrate differences in their use of adaptive and maladaptive behavioural strategies whilst performing tasks, which partly influence their performance outcomes. Key words: autism spectrum disorder, behavioural regulation, cognitive load.